System Quality Development and Analysis Seminar Management Information Web-Based in Department of Education Electronic Engineering and Information - Kusaini, Ghofarudin (Institute of Computer Science (IOCS), 2024)
This study aims to: 1) develop a web-based seminar management information system. 2) determine the quality level of the web-based seminar management information system developed. The research method used in this study is Research and Development (R&D) with a waterfall development model that refers to the rules of software engineering Pressman (2010). The stages that are passed are communication (communication), planning (planning), modeling (modeling), construction (construction), and distribution (deployment). Software quality analysis is carried out by adopting the ISO 25010 standard, namely aspects of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The results of this study are 1) the seminar management information system was built using the PHP programming language and the Postgre database. The frameworks used are CodeIgniter and AdminLTE (Bootstrap). This information system has 7 levels of users, namely administrator, committee (committee), reviewer, main speaker (presenter), second speaker (non-presenter), participant (audience), and visitor (guest). 2) the results of the analysis of software quality by adopting the ISO 25010 standard are as follows: (1) function suitability aspects with 100% success; (2) the performance efficiency aspect obtained a Yslow score of 92.97 (grade A); (3) the compatibility aspect can run well on the 4 tested web mails; (4) the usability aspect obtained a raw SUS score of 73.00, acceptability ranges with acceptable results, grade scale with C results, and adjective ratings with good results; (5) reliability aspect with 100% result; (6) security aspect with the result of security vulnerability being at level 1 (low); (7) maintainability aspect with maintainability index result 90.81 (high category); (8) the portability aspect can run well on the 5 web browsers tested.